Gambaran Intensitas Nyeri Saat Pengambilan Sampel Darah Paska Pemberian Napas dalam di IGD RS Sari Asih Karawaci - Siti Masamah; Ahmad Ikhlasul Amal; Retno Setyawati (PPNI UNIMMAN, 2026)
Blood sampling is a mildly invasive medical procedure aimed at detecting diseases, assessing organ function, and evaluating the patient's overall health. It often causes pain, which can affect patient comfort. Pain perception during this procedure is influenced by both physiological and psychological factors. Therefore, safe and easily implemented non-pharmacological interventions are essential to alleviate pain intensity, and one such intervention is deep breathing relaxation. This descriptive observational study employed a quantitative one-shot case study design with a posttest-only approach. Pain intensity was measured after the deep breathing relaxation intervention was given, without any pretest. The findings revealed that after the deep breathing relaxation intervention, most respondents experienced mild pain (84 people, 70.6%), moderate pain (32 people, 26.9%), and severe pain (2 people, 1.7%). The results indicate that deep breathing relaxation significantly reduces pain intensity during blood sampling and can be effectively used as a non-pharmacological intervention to enhance patient comfort during medical procedures.